Theoretical research of couple stress effect and surface roughness on lubrication regimes transition of misaligned hydrodynamic journal. (December 2022) - Zheng, Liangyan; Zhu, Hanhua; Fan, Shidong; Wu, Jie; Cao, Jiyin
The purpose of this paper was to investigate the combined effects of couple stress and surface roughness on lubrication performance and regime transition of misaligned hydrodynamic journals. New lubrication models considering misalignment angle, couple stress, and surface roughness were established. Under the multi-coupled factors, Stribeck curves were exploited to reveal the lubrication regimes of journals. Following Greenwood's aspect contact theory, force relational equations among external load, asperity support capacity, and oil film bearing capacity have been further discussed. Results showed that the growth of the minimum film thickness, the maximum film pressure, and friction coefficient versus couple stress parameters trended to be opposite to those versus misalignment angle. The speed of the lubrication regime transition and the minimum friction coefficient increased with the enlargement of the misalignment angle but decreased as the couple stress parameter increased. Higher couple stress parameters resulted in an increment of the safety speed of the journal and were conducive to maintaining the hydrodynamic lubrication regime of the misaligned bearing at low speed, which is applicable to such misaligned journal bearings in practical engineering.